REVOLVING DOORS? AN INVESTIGATION INTO THE DETERMINANTS OF SATISFACTION AND TURNOVER AMONG BARBADIAN NEWSPAPER JOURNALISTS - LaCorbiniere, Jason M. (2009)
The purpose of this study was twofold. The first aim was to examine the determinants of job satisfaction and motivation among Barbadian newspaper journalists using two interpretations of the Herzberg (1959) motivator-hygiene model of job motivation. The second aim was to investigate the existing levels of satisfaction in the industry and to analyse the relationship between satisfaction and the intention to turnover. To address these research aims, journalists were surveyed using a comprehensive survey questionnaire constructed from the relevant subscales of various well-tested survey tools. Thirty-one journalists from the two local newspaper firms participated in the survey.